Varovalni gozdovi rdečega bora (Genisto januensis-Pinetum sylvestris) in puhastega hrasta ter črnega gabra (Querco-Ostryetum carpinifoliae) na Boču - Cimperšek, Mitja (Gozdarski vestnik, 2005)
The steep sunny limestone slopes of the western part of Boč are covered by permanent protective forests, which are characterised by two specific xerothermic communities: pine forest with Genista januensis (Genisto januensis-Pinetum sylvestris Tomažič 1940 var. geogr. Sesleria sadleriana var.geogr. nova) and by scrub consisting of pubescent oak and hop hornbeam with Sesleria sadleriana (Querco-Ostryetum carpinifoliae Horvat 1938 var. geogr. Sesleria sadleriana var. geogr. nova). The wood production function of these forests is small, but their ecological and environmental protection functions are great.
Keywords: Boč; črni gaber; fitocenologija; puhasti hrast; rdeči bor; Slovenija; varovalni gozd